That thing we call a heart - Karim, Sheba (HarperTeen, An Imprint of HarperCollins Publishers, 2017)
"This young adult novel by Sheba Karim, author of Skunk Girl, is a funny and affecting coming-of-age story for fans of Jenny Han, Megan McCafferty, and Sara Farizan. Shabnam Qureshi is facing a summer of loneliness and boredom until she meets Jamie, who scores her a job at his aunt's pie shack. Shabnam quickly finds herself in love, while her former best friend, Farah, who Shabnam has begun to reconnect with, finds Jamie worrying. In her quest to figure out who she really is and what she really wants, Shabnam looks for help in an unexpected place--her family, and her father's beloved Urdu poetry. That Thing We Call a Heart is a funny and fresh story about the importance of love - in all its forms."--Amazon.